ANALYSIS OF THE IMPLEMENTATION OF DIAGNOSTIC ASSESSMENT IN SPECIAL EDUCATION SCHOOLS - Safaruddin Safaruddin; Budi Susetyo; Imas Diana Aprilia; Iding Tarsidi; Falentina Syaulatiah (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2026)
This study examined the implementation of diagnostic assessment in Special Education Schools. It employed a qualitative descriptive approach to explore how diagnostic assessment was conducted, utilized, and interpreted in instructional practice. Data were collected through document analysis, classroom observations, and interviews with relevant participants. The findings showed that diagnostic assessment was implemented through observation, individual records, and student portfolios. Observation emerged as the dominant method because it allowed teachers to identify students’ behavioral, academic, and socio-emotional conditions in authentic learning contexts. However, the assessment results were not systematically used as the basis for instructional planning or the development of Individualized Education Programs (IEPs). Instead, the data were often treated as administrative records rather than as evidence for pedagogical decision-making. The study also identified several challenges, including limited teacher assessment literacy, unstandardized documentation practices, and insufficient collaboration with parents. These findings indicated the presence of an assessment–instruction gap, in which assessment data were collected but not optimally translated into adaptive and individualized teaching strategies. Therefore, diagnostic assessment needed to be strengthened as an integrated pedagogical tool to support evidence-based instruction in special education.